Functional echocardiography in the preterm infant - JAMES, ADAM TODD (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2018)
From our research we have shown that myocardial function assessment using tissue Doppler derived strain, strain rate, torsion and fractional area change is both feasible and reliable. We applied these novel echocardiographic markers to assess certain disease states such as assessment of a patent ductus arteriosus, chronic lung disease, treatment with antenatal magnesium sulphate as well as longitudinal follow up over the early neonatal period and found that they may be a useful tool as part of a comprehensive functional myocardial assessment in the preterm population. With the advancement in echocardiography and the continued widespread use for the assessment of the preterm infant these tools may pave the way forward for its clinical use in aiding the diagnosis and management of pathological conditions of preterm infants to improve both morbidity and mortality.
APPROVED
Keywords: strain rate; strain; tissue doppler; echocardiography; torsion; cardiac function; prematurity; preterm